THE ROLE OF INFORMAL EDUCATION IN SUPPORTING THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM THROUGH DEEP LEARNING: A CASE STUDY IN RT 36 GUNUNG KELUA VILLAGE, SAMARINDA CITY: PERAN PENDIDIKAN INFORMAL DALAM MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA MELALUI PEMBELAJARAN MENDALAM (DEEP LEARNING): STUDI KASUS DI RT 36 KELURAHAN GUNUNG KELUA KOTA SAMARINDA - Grace Elsa Roslin; Sri Wahyuni; Muhamad Alisalman; Ady Setiawan (SOSIOEDUKASI, 2025)
This research aims to describe the forms and strategies, as well as challenges of informal education in families that contribute to the implementation of the Independent Curriculum, especially in supporting deep learning. The research was conducted in RT 36, Gunung Kelua Village, Samarinda City, with a qualitative approach of case studies. Data collection techniques were carried out through interviews, observations, and documentation studies. The informants were determined purposively, consisting of the Chairman of RT 36 as the key informant, five parents as the main informant, and five students from the elementary to vocational school levels as supporting informants. Data analysis was carried out using the Miles & Huberman model with stages of data reduction, data presentation, and conclusion drawn, while validity was maintained through triangulation of techniques and sources, member checking, and trail audits. The results of the study show that: (1) The form and strategy of informal education in supporting the implementation of the Independent Curriculum through deep learning are found to be four forms and informal education, namely home learning assistance, the use of technology and digital media, contextual learning practices at home, and the habit of independent learning (2) Challenges faced in implementing informal education such as parental understanding that has not yet been equally regarding the principles of the Independent Curriculum and deep learning, time and knowledge limitations, and learning facilities and environment. These findings demonstrate the important role of families in supporting the implementation of the Independent Curriculum and encouraging deep learning, while highlighting the need for continued support from schools, communities, and policy makers for informal education to run sustainably and effectively.